2009
DOI: 10.2752/175303708x390455
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Changes in Oxytocin Levels in Men and Women Before and After Interaction With a Bonded Dog

Abstract: Oxytocin (OT) is a neuropeptide increasingly recognized for its role in bonding, socialization, and stress relief. Previous research has demonstrated participants' OT levels increased after interacting with or petting a dog, suggesting OT is at least partially responsible for the calm, relaxing feeling that participants experienced during this intervention. The purpose of our study was to more closely examine changes in oxytocin levels in men and women in response to interaction with their own dog after being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
144
2
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 229 publications
(157 citation statements)
references
References 32 publications
8
144
2
3
Order By: Relevance
“…If the respondents experience a release of oxytocin when in contact with their dogs, they may develop the same attachment to the dog as to a child, which is consistent with their respondents. Miller et al [16] found that this effect was only significant in women, although in the present study, the male participant possibly seemed even more attached to his dogs than the rest of the group. This may be attributable to the fact that he had a smaller human network, but if not, oxytocin alone cannot explain the attachment.…”
Section: Discussioncontrasting
confidence: 46%
See 1 more Smart Citation
“…If the respondents experience a release of oxytocin when in contact with their dogs, they may develop the same attachment to the dog as to a child, which is consistent with their respondents. Miller et al [16] found that this effect was only significant in women, although in the present study, the male participant possibly seemed even more attached to his dogs than the rest of the group. This may be attributable to the fact that he had a smaller human network, but if not, oxytocin alone cannot explain the attachment.…”
Section: Discussioncontrasting
confidence: 46%
“…The other theory that has emerged from recent research is that contact with animals causes humans to release the peptide hormone oxytocin, just as they do when they care for or nurse an infant [16] . This hormone is known to reduce stress and anxiety.…”
mentioning
confidence: 99%
“…Several studies documented that human-animal interactions have the potential to increase oxytocin levels in humans (e.g., Odendaal & Meintjes, 2002;Miller, Kennedy (2012) proposed that most of the positive physiological, psychological and social effects of animals on human well-being are mediated via the activation of the oxytocin system. Especially the stress-and anxiety-reducing effects that result from a release of oxytocin in response to animal contact were suggested to be a core mechanism underlying many of these effects (Beetz, Uvna¨s-Moberg, et al, 2012).…”
mentioning
confidence: 99%
“…Oxytocin coordinates both the causes and the effects of positive social interactions, and it can be conditioned to the psychological state or imagery of people. An increase in the beneficial hormone oxytocin is also observed when humans interact with pet animals (Handlin, 2010;Miller et al, 2009;Odendaal & Meintjes, 2003). In the PhD-thesis of Handlin (2010), ten female dog owners and their male Labrador dogs participated together with ten controls.…”
Section: Animals As Contributors To Reduced Arousal Anxiety and Depmentioning
confidence: 99%